Generation of Rainfall Intensity-Duration Frequency Models for Port Harcourt City in South- South Ngeria - Emeka-Chris, C. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Inadequate meteorological data poses a significant challenge for engineers in accurately designing, operating, and planning water resources, particularly against extreme rainfall events. This study focuses on Generating Intensity Duration Frequency (IDF) Models for Port Harcourt City in South Nigeria. Daily rainfall data spanning thirty-two years (1983-2014) were collected from the Nigeria Meteorological Agency (NIMET) Oshodi, Lagos State. The annual maximum series method was employed to select datasets for rainfall analysis.Two statistical distributions, Gumbel and Log Pearson Type III, were utilized to calculate observed rainfall intensity values at durations of 10, 15, 20, 30, 60, 120, 180, 240, 300, and 360 minutes, considering return periods of 2, 5, 10, 20, 50, and 100 years. Non-linear regression analysis using Microsoft Excel's Optimization Technique Solver wizard was performed to derive parameters for the IDF models for each duration and return period. Metrics such as chi-square (χ2), coefficient of determination (R2), and Root Mean Square Error (RMSE) were analyzed in order to assess the performance of the models. For the Gumbel distribution, R2 values ranged from 0.76 to 1.00, with RMSE from 0.20 to 11.73. The Log Pearson Type III distribution showed perfect R2of 1 and RMSE ranging from 0.23 to 9.68, indicating superior performance in terms of R2 and RMSE.While there were no significant differences among the predicted intensities of various IDF models, the Log Pearson Type III Model is recommended for predicting rainfall intensities in Port Harcourt due to its superior performance metrics. These IDF Models serve as valuable tools for engineers and hydrologists in estimating stormwater runoff, designing drainage systems, managing reservoirs, and planning water resources development to mitigate flooding and its impacts. Moreover, they can enhance the teaching of land drainage courses for engineering students, providing practical demonstrations and improving their understanding of the subject matter.